ADAPTING UKRAINIAN SPACE LAW TO THE CHALLENGES OF THE NEW SPACE ERA - Rokytsky, Yevgen (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
The article is devoted to the analysis of the legal and institutional mechanisms of regulation of strategically important space activities in Ukraine. Research methods: the scientific-theoretical research methods of abstraction, idealization, construction of hypotheses and models, documentary analysis and synthesis, objective truth, cognitive-analytical etc. Results: the origin and historical genesis of legal regime of the space activities in Ukraine, constituent elements of legal mechanism of the development of space industry and the problems of adapting this mechanism to the trends of the «new space”, are analyzed. The author suggests adapting the law, and some elements of such adaptation, to create the optimal legal framework of Ukrainespace industry development. The scientific aim of this article is to contribute to the development of the adequate and integrated regulation of space industry in Ukraine, to improve the quality and to ensure the effectiveness of legal regulation of space relations and to theoretically develop the concept of the adaptation of the national space law. Discussion: the evolution of the national space law is analyzed on the background of Ukraine’s space industry development and trends of the New Space. The law needs not a fragmentary. but a comprehensive adaptation, with regard to the peculiarities of the developments of the national space law of Ukraine and its prospective partners.